Synergism of Carbenicillin and Gentamicin Against Enterococci - Libke, Robert D. (1973)
Carbenicillin and gentamicin were tested for synergism against 25 strains of enterococci by two different methods. Killing curves were determined by doing serial colony counts of broth cultures containing the antibiotics separately and in combination. The combination was synergistic for all 25 strains with 75 and 4 μg of carbenicillin and gentamicin per ml, respectively. Reducing the concentrations to 50 and 3 μg of the antibiotics per ml with four strains significantly reduced the rate of killing of the combination. Synergism was also studied by constructing isobolograms, by using the standard two-dimensional broth dilution checker-board technique, and by measuring the end points both for minimal inhibitory concentrations (MICs) and minimal bactericidal concentrations (MBCs). Synergism was present for all 25 strains when bactericidal end points (MBCs) were evaluated, but was present for only 7 of the 25 strains when MICs were used to construct isobolograms. The time and effort involved were roughly the same for killing curves and for isobolograms, and it was concluded that neither had a distinct advantage over the other.